(untitled) (Research, Society and Development, 2022)
Over-the-counter non-steroidal anti-inflammatory drugs (NSAIDs) are among the most prescribed drug classes in the world to treat inflammation, pain and swelling, osteoarthritis, rheumatoid arthritis and musculoskeletal disorders, inhibiting prostaglandins by blocking cyclooxygenases (COX). The aim of this study was to collect information on the adverse effects of prolonged and indiscriminate use of non-steroidal anti-inflammatory drugs: diclofenac versus ibuprofen. Methodology: Bibliographic review study of articles obtained from the electronic databases SCIELO, LILACS, MEDLINE/PUBMED, where the exclusion and inclusion criteria were reviewed, resulting in 25 studies included. The results show that some adverse reactions may occur due to the irrational use of NSAIDs. susceptibility and habit of self-administering NSAIDs that inhibit COX enzymes, resulting in various acute or chronic kidney and gastrointestinal injuries. The appropriate choice of an NSAID in the treatment must be individualized for each patient, taking into account their risk and benefit factors and the desired therapeutic efficacy, and its rational use is an important ally of clinicians in promoting the health and well-being of patients.